2007
DOI: 10.1021/jf0712503
|View full text |Cite
|
Sign up to set email alerts
|

Onions: A Source of Unique Dietary Flavonoids

Abstract: Onion bulbs (Allium cepa L.) are among the richest sources of dietary flavonoids and contribute to a large extent to the overall intake of flavonoids. This review includes a compilation of the existing qualitative and quantitative information about flavonoids reported to occur in onion bulbs, including NMR spectroscopic evidence used for structural characterization. In addition, a summary is given to index onion cultivars according to their content of flavonoids measured as quercetin. Only compounds belonging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
359
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 527 publications
(406 citation statements)
references
References 82 publications
(135 reference statements)
21
359
0
6
Order By: Relevance
“…It has also been suggested that long day onion cultivars of Rijnsburger type from Northern Europe have higher levels of quercetin glucosides than short day onions of North American and Japanese origin [161]. In a study on 16 European onion varieties levels of quercetin glycosides in the edible parts were highest in the red onion cv.…”
Section: Crop and Cultivarmentioning
confidence: 99%
“…It has also been suggested that long day onion cultivars of Rijnsburger type from Northern Europe have higher levels of quercetin glucosides than short day onions of North American and Japanese origin [161]. In a study on 16 European onion varieties levels of quercetin glycosides in the edible parts were highest in the red onion cv.…”
Section: Crop and Cultivarmentioning
confidence: 99%
“…In red onions anthocyanins are also present. These are primarily cyanadin glucosides acylated with malonic acid or non-acylated [39,133,161].…”
Section: Crop and Cultivarmentioning
confidence: 99%
“…Levels of flavonols vary considerably between onion cultivars with reported levels ranging from 2549 quercetin equivalents per kg fresh weight (FW) in the red onion cultivar Karmen to <1 quercetin equivalents in the white onion cultivar Contessa [161]. A study by Lombard et al (2005) examined the total flavonol content in 5 onion varieties and found significantly higher concentrations in red skinned onion varieties compared to yellow varieties [37].…”
Section: Crop and Cultivarmentioning
confidence: 99%
See 1 more Smart Citation
“…Onions are a unique source of dietary flavonoids and other bioactive substances (Corzo-Martínez et al 2007;Griffiths et al 2002;Lanzotti 2006;Slimestad et al 2007;Rodriguez et al 2009Rodriguez et al , 2010 and there has been in vivo evidence for the hypolipidemic and antioxidant effects of onion consumption (Park et al 2007;Vidyavati et al 2010). It is estimated that more than 450,000 tonnes of onion solid waste is produced each year in Europe (Moure et al 2001).…”
Section: Introductionmentioning
confidence: 99%